Immunohistochemical analysis of RTKs expression identified HER3 as a prognostic indicator of gastric cancer. Issue 12 (3rd December 2014) - Ema, Akira; Yamashita, Keishi; Ushiku, Hideki; Kojo, Ken; Minatani, Naoko; Kikuchi, Mariko; Mieno, Hiroaki; Moriya, Hiromitsu; Hosoda, Kei; Katada, Natsuya; Kikuchi, Shiro; Watanabe, Masahiko
<x xml:space="preserve">Abstract</x> We performed both clinico‐pathological and prognostic analysis of RTKs in gastric cancer. Among these, HER3 was identified as independent prognostic indicator. <boxed-text content-type="graphic" id="cas12556-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>